2021
DOI: 10.1155/2021/9628675
|View full text |Cite
|
Sign up to set email alerts
|

Study on Dynamic Mechanical Properties and Failure Mechanism of Sandstones under Real-Time High Temperature

Abstract: The research on dynamic mechanical properties of rocks under high temperature is the basis for safe and efficient implementation of deep coal mining and underground coal gasification engineering. In this paper, the split Hopkinson bar (SHPB) with real-time high-temperature function was adopted to systematically study dynamic mechanical properties of sandstones. The research showed that under the condition of a fixed temperature, with the increase of strain rate, the dynamic compressive strength and dynamic pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Xu et al 19 investigated the thermal effect on rock fragmentation characteristics of Laurentian granite using a dynamic ball compression test and concluded that dynamic tensile strength is continuously decreasing with increasing temperature due to thermal damage. Furthermore, Zhang et al 20 found an increasing trend in the compressive strength of sandstone up to 400 °C, which then decreased with increasing temperature. Fan et al 21 evaluated the three cooling methods on the dynamic properties of sandstone and concluded that compressive strength increases up to 200 °C and sharply reduces afterwards for natural cooling due to the improved compactness of sandstone.…”
Section: Introductionmentioning
confidence: 98%
“…Xu et al 19 investigated the thermal effect on rock fragmentation characteristics of Laurentian granite using a dynamic ball compression test and concluded that dynamic tensile strength is continuously decreasing with increasing temperature due to thermal damage. Furthermore, Zhang et al 20 found an increasing trend in the compressive strength of sandstone up to 400 °C, which then decreased with increasing temperature. Fan et al 21 evaluated the three cooling methods on the dynamic properties of sandstone and concluded that compressive strength increases up to 200 °C and sharply reduces afterwards for natural cooling due to the improved compactness of sandstone.…”
Section: Introductionmentioning
confidence: 98%
“…Li et al [18] found a correlation between the various patterns of energy dissipations and the development of microcracks. In the study of Zhang et al [19], the energy dissipation density as an important parameter of the damage variable can better express the dynamic stress-strain relationship of sandstones under real-time high temperatures. In evaluating energy, energy consumption density as a standard metric has its disadvantage in describing the time effect.…”
Section: Introductionmentioning
confidence: 99%